2013
DOI: 10.1128/aac.00624-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cell-Penetrating Peptides That Are Bactericidal to Neisseria meningitidis and Prevent Inflammatory Responses upon Infection

Abstract: bMeningococcal disease is characterized by a fast progression and a high mortality rate. Cell-penetrating peptides (CPPs), developed as vectors for cargo delivery into eukaryotic cells, share structural features with antimicrobial peptides. A screen identified two CPPs, transportan-10 (TP10) and model amphipathic peptide (MAP), with bactericidal action against Neisseria meningitidis. Both peptides were active in human whole blood at micromolar concentrations, while hemolysis remained negligible. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 66 publications
0
17
1
Order By: Relevance
“…aureus and Neisseria meningitides ( N . meningitides ) . However, its potential use against multi‐drug resistant bacteria with high separation rates when isolated from clinics has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus and Neisseria meningitides ( N . meningitides ) . However, its potential use against multi‐drug resistant bacteria with high separation rates when isolated from clinics has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Transportan 10 (TP10) is a deletion analogue of the CPP transportan, a 21-residue chimeric construct consisting of the N-terminal part of the neuropeptide galanin linked to the full-length wasp venom peptide mastoparan that lacks the toxic side effects of its parent peptide. TP10 can transport cargo across cell membranes [10,11] and it has been reported that TP10 can enter both mammalian and microbial cells, preferentially permeabilising and killing microbes such as S. aureus and Neisseria meningitides (N. meningitides) [6,9]. However, its potential use against multi-drug resistant bacteria with high separation rates when isolated from clinics has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1B), thus, rendering the bacteria resistant to physiologically relevant concentrations of LL-37 (Schaller-Bals et al, 2002). The abrogation of selective host-cell Oehlke et al (1998); Palm et al (2006); Eriksson et al (2013). b.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of CPF-C1 and several of its analogs to decrease bacterial quantities was approximated in an in vivo infection example in mice using a prior established method. [30,31] In summary, female Kunming mice (18-22 g; Medical Experimental Animal Center, Lanzhou University, China) were maintained in a 12-hr light-dark cycle with an unlimited supply of water and food. The mice were challenged intraperitoneally with 1.2 × 10 8 CFU of E. coli ATCC 25922 or E. coli 780 cells in 100 μl of 0.9% NaCl (normal saline or NS).…”
Section: In Vivo Antimicrobial Activitymentioning
confidence: 99%